Implementation of Islamic Business Ethics in Marketing Sofa Products at ACC Furniture Jambi - Marlina; Wargo; Kuswanto (Zabags International Journal of Islamic Studies, 2025)
Islamic business ethics fundamentally emphasize honesty, trustworthiness, justice, and transparency in all economic activities, including marketing practices. Amid intensifying market competition, the application of Islamic business ethics serves not only as a moral compass but also as a strategic lever to build consumer trust and strengthen competitive advantage. This study analyzes the implementation of Islamic business ethics in marketing sofa products at ACC Furniture Jambi, focusing on how the firm’s marketing strategies align with Sharia principles. Employing a qualitative case study approach, data were collected through interviews, observations, and documentation, and analyzed descriptively via data reduction, display, and conclusion drawing. The findings indicate that ACC Furniture Jambi applies marketing strategies encompassing segmentation, targeting, positioning, differentiation, and the marketing mix, supported by ethical practices such as transactional honesty, rejection of false oaths, courteous service, adherence to halal principles, and avoidance of riba. These results demonstrate that embedding Islamic business ethics enhances brand credibility, strengthens customer loyalty, and contributes to the literature on Islamic marketing, while offering practical guidance for small and medium enterprises to integrate Sharia values into their marketing strategies.